INFLUENCE OF EDGE REINFORCING RING ROTATION ON LOAD CARRYING CAPACITY OF CONICAL SHELLS LOADED BY EXTERNAL PRESSURE (Perner's Contacts, 2022)
The aim of the article is to present a part of the problem of calculating the load carrying capacity of conical shells, which by their dimensions and selected boundary conditions do not comes under within the scope the standards. The investigated conical shells have a semi vertex angle in the range of 75 ° - 85 ° and are provided with a reinforcing ring at the lower edge. When the conical shells are loaded by external pressure, not only does the edge ring move in the radial direction, but also its rotation (the moment has the direction of the tangent to the edge of the cone). This paper addresses the question of how this rotation affects the overall load capacity of a conical shell. Due to the fact that the investigated shell structures cannot be solved using standard methods and procedures, this problem is solved by means of numerical analyzes and experiments. Based on the results of numerical analyzes of the load carrying capacity of conical shells with different boundary conditions, the suitability of using simplified numerical models and samples for performing experiments was verified.